2011
DOI: 10.1249/mss.0b013e3182155d21
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Exercise, Fitness, and Performance Genomics in 2010

Abstract: This review of the exercise genomics literature emphasizes the strongest papers published in 2010 as defined by sample size, quality of phenotype measurements, quality of the exercise program or physical activity exposure, study design, adjustment for multiple testing, quality of genotyping, and other related study characteristics. One study on voluntary running wheel behavior was performed in 448 mice from 41 inbred strains. Several quantitative trait loci for running distance, speed, and duration were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 62 publications
1
85
0
6
Order By: Relevance
“…However the study supported the decade long hypothesis for encouraging the ectmorphic mesomorph body type for the of Track and Field athletes with higher reciprocal Ponderal index [38]. Other studies also showed that mesomorphic component was a dominant characteristic of somatotype for Track and Field athletes compare to other two components [4,5,6,7,8,37,38].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However the study supported the decade long hypothesis for encouraging the ectmorphic mesomorph body type for the of Track and Field athletes with higher reciprocal Ponderal index [38]. Other studies also showed that mesomorphic component was a dominant characteristic of somatotype for Track and Field athletes compare to other two components [4,5,6,7,8,37,38].…”
Section: Discussionsupporting
confidence: 70%
“…Requirement of specific physique for good performance in sports had been supported by different studies [1]. Various studies had been attempted to relate performance level with body type and body composition [2,3,4,5,6]. Relationship between the leg length and performance level during running had been established by different studies [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies (e.g., (4,11,31,33) were based on a case-control design and were characterized by the same limitations that we highlighted last year (19), and which were further addressed in a recent publication (8). Although some studies had replication data, the small sample size and the lack of clearly defined physiological phenotypes were consistent limiting factors (21,32).…”
Section: Endurance Performancementioning
confidence: 99%
“…This investigation is a subset of the FAMuSS study which is the largest study that has investigated candidate genes associated with muscle performance, and the first study to specifically investigate NOS3 variant associations with PA and muscle strength in humans [15]. Furthermore, FAMuSS 6 ISRN Vascular Medicine meets the criteria outlined by Hagberg et al [14,47] that are necessary for conducting exercise genomics studies including a large sample size, a well-structured exercise intervention with stringent assessment of phenotypes, and quality control of genotyping.…”
Section: Nos3 +894 G>tmentioning
confidence: 99%